Resilience capacities as perceived by European farmers. (October 2021) - Spiegel, Alisa; Slijper, Thomas; de Mey, Yann; Meuwissen, Miranda P.M.; Poortvliet, P. Marijn; Rommel, Jens; Hansson, Helena; Vigani, Mauro; Soriano, Bárbara; Wauters, Erwin; Appel, Franziska; Antonioli, Federico; et al.
Abstract: CONTEXT: The ability of a farm to cope with challenges is often conceptualised as resilience. Although improving resilience of farms is a major policy goal in the European Union, the current state of resilience is often unknown. Previous resilience assessments have been based either on pre-defined indicators or on perceptions. In particular, empirical research of perceived resilience is still limited and usually restricted to one specific resilience capacity, one challenge, or one function. OBJECTIVE: We investigate how European farmers perceive resilience capacities of their farms. Extending beyond previous research, we cover all three resilience capacities (robustness, adaptability, and transformability), consider a broad range of short-term shocks and long-term stresses, and include multiple functions. Furthermore, we analyse farms from diverse farming systems across Europe and investigate whether farms and farmers with similar perceived resilience capacities share characteristics. METHODS: We address the complex nature of resilience capacities by accounting for multiple scales formulated as analytical steps of a resilience assessment framework. More specifically, these are 'resilience of what' (farms and farming systems), 'resilience to what' (challenges), 'resilience for what purpose' (functions), and 'what enhances resilience' (resilience attributes). These steps guided the development of a survey with farmers across eleven European farming systems. Based on three indices for each farmer indicating perceived robustness, adaptability, and transformability of their farms, we identified two classes of farmers with particularly strong and weak resilience profiles respectively. Using nonparametric Mann-Whitney U tests, we furthermore compared other parameters collected via the survey across the identified classes. RESULTS AND CONCLUSIONS: Our data sample outputs two classes of similar size characterised by all three perceived resilience capacities being above (below) regional average. This finding suggests that the perceptions of robustness, adaptability, and transformability are mutually dependent. Furthermore, we found that farmers who perceive their resilience above the regional averages are characterised by lower risk aversion, greater focus on providing public goods, a higher number of implemented risk management strategies, more active involvement in networks, and greater openness to innovation. SIGNIFICANCE: The revealed links between particular characteristics of farms and farmers and different levels of perceived resilience capacities can support policy-makers in developing more targeted resilience-enhancing strategies, as well as in understanding farmers' responses to challenges. Finally, our results can serve as a basis for further research, e.g., for formulating and testing hypotheses on causal effects between perceived resilience and its components, and on links between perception- and indicator-based resilience assessments. Graphical abstract: Unlabelled Image Highlights: We investigate how European farmers perceive robustness, adaptability, and transformability of their farms. Our results indicate mutual dependence between the three perceived resilience capacities. Two groups of farm( er )s are revealed based on the resilience capacities: all three below and all three above regional means. Each group shares characteristics, such as labour input, risk aversion, and perceived importance of private and public goods.